Demethylation of H3K9 and H3K27 Contributes to the Tubular Renal Damage Triggered by Endoplasmic Reticulum Stress - Paula Diaz-Bulnes; Maria Laura Saiz; Viviana Corte-Iglesias; Raúl R Rodrigues-Diez; Aida Bernardo Florez; Cristian Ruiz Bernet; Cristina Martin Martin; Marta Ruiz-Ortega; Beatriz Suarez-Alvarez; Carlos López-Larrea (MDPI AG, 2022)
Loss of protein homeostasis (proteostasis) in the endoplasmic reticulum (ER) activates the unfolded protein response (UPR), restoring correct protein folding. Sustained ER stress exacerbates activation of the major UPR branches (IRE1α/XBP1, PERK/ATF4, ATF6), inducing expression of numerous genes involved in inflammation, cell death, autophagy, and oxidative stress. We investigated whether epigenetic dynamics mediated by histone H3K9 and H3K27 methylation might help to reduce or inhibit the exacerbated and maladaptive UPR triggered in tubular epithelial cells. Epigenetic treatments, specific silencing, and chromatin immunoprecipitation assays were performed in human proximal tubular cells subjected to ER stress. Pharmacological blockage of KDM4C and JMJD3 histone demethylases with SD-70 and GSKJ4, respectively, enhanced trimethylation of H3K9 and H3K27 in the ATF4 and XBP1 genes, inhibiting their expression and that of downstream genes. Conversely, specific G9a and EZH2 knockdown revealed increases in ATF4 and XBP1 expression. This is a consequence of the reduced recruitment of G9a and EZH2 histone methylases, diminished H3K9me3 and H3K27me3 levels, and enhanced histone acetylation at the ATF4 and XBP1 promoter region. G9a and EZH2 cooperate to maintain the repressive chromatin structure in both UPR-induced genes, ATF4 and XBP1. Therefore, preserving histone H3K9 and H3K27 methylation could ameliorate the ER stress, and consequently the oxidative stress and the triggered pathological processes that aggravate renal damage.